Factors associated with the stigma-discrimination complex towards healthcare workers among university students during the coronavirus pandemic in Mexico - Cassiani-Miranda, Carlos; Arismendy-López, Yinneth; Álvarez-Solorza, Isabel; Toxqui-Tlachino, María; Campo-Arias, Adalberto; Tirado-Otálvaro, Andrés; Bustamante-Montes, Lilia Patricia (Universidad y Salud, 2022)
Introduction: COVID-19-related stigma towards healthcare professionals negatively influences their job performance and well-being, however, this issue has not been sufficiently investigated. Objective: To determine the frequency and variables associated with COVID-19-related stigma toward health care workers in a university population in Mexico. Materials and methods: Cross-sectional study. An online questionnaire was sent to 1,054 students between 18 and 29 years of age. Demographic variables, religiosity, fear of COVID-19 and its association with COVID-19-related stigma-discrimination towards health workers (dependent variable) were analyzed. Bivariate analysis and a generalized linear model were performed to calculate adjusted prevalence ratios. Results: The proportion of high stigma-discrimination was 12.4% and was associated with high fear of COVID-19 RPa= 1.51 (95% CI 1.06 - 2.23). Conclusion: the findings highlight the importance of establishing programs to reduce COVID-19-related stigmatization towards healthcare professionals.